ENGLISH TEACHERS' STRATEGIES IN TEACHING READING COMPREHENSION IN THE FORM OF HYBRID LEARNING - Marsiana Nanda Alvionita; citra Kusumaningsih; Elly Syahadati (IKIP PGRI Pontianak, 2022)
This researcher aims to determine the strategies used by teachers in teaching reading comprehension during the hybrid learning period in implementing this strategy at SMAS Karya Budi Putussibau. This researcher involved only 1 school located in an urban area. This researcher used a descriptive type of research with a qualitative approach. Collecting data using semi-structured interviews and an Observation checklist, with interview tools using interview guidelines. In this research, there was 1 school involved, namely SMAS Karya Budi Putussibau. The informants chose 2 respondents, namely the English teacher. This data collection tool is carried out by telephone which is carried out face-to-face (offline). It was used to support this interview data and observation checklist. Then, these results were analyzed to answer the research problem by collecting through interview guidelines and knowing its relevance, so that they could explore and obtain information contained in schools, especially about teachers' strategies in teaching reading comprehension during hybrid learning classes. This researcher found two strategies used by English teachers at SMAS Karya Budi Putussibau in teaching reading comprehension during hybrid learning classes. The first strategy is Think-Aloud and the second strategy is Question-Answer Relationship (QARs). Applying this strategy, can also improve students' reading comprehension and improve students' reading ability to find main ideas, especially in reading English both inside and outside the classroom during the hybrid learning period.